Difference between received and expected knowledge of patients undergoing knee or hip replacement in seven European countries - Klemetti, Seija; Leino-Kilpi, Helena; Cabrera, Esther; Copanitsanou, Panagiota; Ingadottir, Brynja; Istomina, Natalja; Katajisto, Jouko; Papastavrou, Evridiki; Unosson, Mitra; Valkeapää, Kirsi (My University, 2015)
Abstract The purpose of the study was to examine received and expected knowledge of patients with knee/hip arthroplasty in seven European countries. The goal was to obtain information for developing empowering patient education. The data were collected (during 2009-2012) from patients (n = 943) with hip/knee arthroplasty prior to scheduled preoperative education and before discharge with the Received Knowledge of hospital patient scale (RKhp) and Expected Knowledge of hospital patient scale (EKhp). Patients' knowledge expectations were high but the level of received knowledge did not correspond to expectations. The difference between received and expected knowledge was higher in Greece and Sweden compared with Finland (p < .0001, p < .0001), Spain (p < .0001, p = .001), and Lithuania (p = .005, p = .003), respectively. Patients' knowledge expectations are important in tailoring patient education. To achieve high standards in the future, scientific research collaboration on empowering patient education is needed between European countries.
Keywords: arthroplasty patients; educational nursing practice; empowering patient education; received knowledge